Sex-Biased CHHs and Their Putative Receptor Regulate the Expression of IAG Gene in the Shrimp Litopenaeus vannamei - Guo, Qing; Li, Shihao; Lv, Xinjia; Xiang, Jianhai; Manor, Rivka; Sagi, Amir; Li, Fuhua (Frontiers in Physiology, 2019)
The “eyestalk-androgenic gland (AG)-testis” endocrine axis is involved in male sexual differentiation of crustaceans. The insulin-like androgenic gland hormone (IAG), secreted from the AG, plays a central role in this axis, however key factors upstream the IAG are still poorly understood. Here, two crustacean hyperglycemic hormone (CHH) genes (LvCHH1 and LvCHH2) and their putative receptor guanylate cyclase (LvGC) were identified in Litopenaeus vannamei. LvCHH1 and LvCHH2 belonged to CHH subfamily I members and LvGC was a membrane-bound guanylate cyclase. They were all differentially expressed in eyestalks and gonads of males and females. RNA interference (RNAi) of either LvCHH1 or LvCHH2 increased LvIAG expression, while injection of their recombinant protein decreased LvIAG expression, indicating that LvCHH1 and LvCHH2 are inhibitory factors of LvIAG expression. Yeast two-hybrid assay showed that both LvCHH1 and LvCHH2 interacted with LvGC while their RNAi and recombinant protein injection exerted opposite regulatory effects on the transcriptional expression of LvGC. Meanwhile, knockdown of LvGC increased LvIAG expression. These results suggest that LvGC is the receptor of LvCHH1 and LvCHH2 and they are all involved in male sexual development by regulating LvIAG expression. The present study unveils missing upstream elements in the “eyestalk-AG-testis” endocrine axis in crustacean.